2010
DOI: 10.1002/clc.20711
|View full text |Cite
|
Sign up to set email alerts
|

Restrictive Right Ventricular Physiology and Right Ventricular Fibrosis as Assessed by Cardiac Magnetic Resonance and Exercise Capacity After Biventricular Repair of Pulmonary Atresia and Intact Ventricular Septum

Abstract: Background: The hypertrophic myocardium, myocardial fiber disarray, and endocardial fibroelastosis in pulmonary atresia and intact ventricular septum (PAIVS) may provide anatomic substrates for restrictive filling of the right ventricle. Hypothesis: Restrictive right ventricle (RV) physiology is related to RV fibrosis and exercise capacity in patients after biventricular repair of PAIVS. Methods: A total of 27 patients, age 16.5 ± 5.6 years, were recruited after biventricular repair of PAIVS. Restrictive RV ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 32 publications
2
14
1
Order By: Relevance
“…Each of the left ventricular (LV) segments will be scored on a 5‐point scale (0–4) , and the maximum LV LGE score was 68. A high concordance in scoring LGE has previously been reported by our group .…”
Section: Methodssupporting
confidence: 86%
“…Each of the left ventricular (LV) segments will be scored on a 5‐point scale (0–4) , and the maximum LV LGE score was 68. A high concordance in scoring LGE has previously been reported by our group .…”
Section: Methodssupporting
confidence: 86%
“…Reports in adults have demonstrated its clinical utility in acute and chronic ischemic heart disease, cardiomyopathies, myocarditis, and ventricular thrombus detection. In CHD, LGE has been described in patients with repaired tetralogy of Fallot [153-155], atrial switch operations for transposition of the great arteries [156], Fontan operations for functionally single ventricles (Figure 14) [157], congenitally corrected transposition of the great arteries [158], aortic valve stenosis [159,160], pulmonary atresia with intact ventricular septum [161], anomalous left coronary artery from the pulmonary artery after repair [162], endocardial fibroelastosis (Figure 15) [163,164], and fibrous tissue along regions of reconstruction in patients who have had surgery for CHD [165]. In the tetralogy of Fallot, atrial switch, and Fontan operation cohorts, the presence of LGE has been associated with adverse ventricular mechanics, exercise intolerance, and ventricular arrhythmias [153,155-158].…”
Section: Introductionmentioning
confidence: 99%
“…A tissue Doppler echocardiographic study has shown regional systolic and diastolic longitudinal myocardial dysfunction involving both the right and left ventricles in adolescent patients after biventricular repair in infancy 94). A subsequent study using 2D speckle tracking imaging confirmed the impairment of RV systolic and diastolic deformation 15). LGE CMR showed evidence of RV myocardial fibrosis.…”
Section: Applications In Congenital Heart Diseasementioning
confidence: 96%
“…On the other hand, persistence of restrictive RV physiology in the long-term has been associated with less progressive dilation of the right ventricle and better exercise capacity 14). Restrictive RV physiology has also been described after biventricular repair of pulmonary atresia with intact ventricular septum (PAIVS) due probably to the relatively small RV cavity and intrinsic myocardial and endocardial abnormalities that reduce RV compliance 15). Limited data also suggest that restrictive RV physiology also predicts better exercise capacity in these patients 15)…”
Section: Ventricular Dysfunction In Congenital Heart Diseasementioning
confidence: 99%